A Note on The Cognitive Abilities Toward Natural Ecosystem of Gifted and Talented Muslim Students - Zainal, R.; Adnan, H.A.; Zahrin, 'Ainnur F.; Saharudin, S.N.A.; Asmuje@Asmuzi, N.F.; Zainun, A.; Yazid, A.F. (Universiti Sains Islam Malaysia, 2024)
Studies on gifted and talented are critically underrated in this leading-edge world. Humans now has become intellectual than ever and along the way has been moving forward ever since. Cognitive abilities including the skill on the memory, attention, reasoning and many more were the best approaches to identified the gifted and talented students. Gifted and talented students have a different level of ability and different levels of cognitive skills, that is known as the measurement of cognitive ability. In the consideration of a previous study that compares the cognitive abilities within two different exposures; natural ecosystem and urban districts, in quest to find the best natural ecosystem to be exposed to gifted and talented Muslim students in Kolej GENIUS Insan. The main objective of this research is to discuss on the cognitive abilities toward ecosystem including forest, river and lake that stimulate gifted and talented students' brain functions. The choice made is based on a verse in the Holy Quran, in which it is said that river is made supposedly to be a nerve-calmer and brain stimulator. The expecting result is that the natural ecosystem will affect more effective on the cognitive ability rather than urban environment.